P90-T Nerve conduction, silent period, anthropometric and metabolic syndrome indices in patients with carpal tunnel syndrome. Issue 7 (July 2019) - Baslo, Sezin Alpaydin; Yusifov, Mahir; Ozturk, Oya; Atakli, Dilek; Baslo, Mehmet Baris
Abstract : Background: Some of the anthropometric features of the hand or wrist are risky for the development of carpal tunnel syndrome (CTS) like the presence of metabolic disorders. This study aims to search the electrophysiological aspect of CTS and its relation to anthropometric measurements as well as to metabolic syndrome (MS) indices. Material and methods: Fifteen healthy participants and 17 patients with CTS were enrolled. Sensory and motor nerve conduction studies of median and ulnar nerves and the "sensitive" comparison tests were performed. Cutaneus silent period (CSP) was searched by stimulating either second or fifth digit while recoding over thenar. Hand and wrist width, wrist depth and palm length were measured. Indices for MS were determined. Results: CTS patients revealed abnormal conduction of median nerve. The only significant anthropometric measure that correlated to electrophysiological aspect of CTS was short palm length. Cutaneus silent period (CSP) was induced in similar rate between the groups likewise the onset latency and duration of CSP. Patients with CTS revealed higher sensory threshold and needed more powerful stimulus on 2nd digit to induce CSP. Anthropometric measures of CTS patients with metabolic syndrome were similar to ones who don't have it. CTS patient with MS revealed slightly lower median motor amplitude and prolonged latency difference between median and ulnar nerves on palmar mixed afferent conduction. Conclusions: CSP can inducible in CTS patients who had preserved sensory and motor responses. Short palm length predicts the presence of CTS. MS slightly affects median nerve conduction in patients with CTS.